Growth curves for Turkish Girls with Turner Syndrome: Results of the Turkish Turner Syndrome Study Group - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP (GALENOS YAYINCILIK, 2015)
Objective: Children with Turner syndrome (TS) have a specific growth pattern that is quite different from that of healthy children. Many countries have population-specific growth charts for TS. Considering national and ethnic differences, we undertook this multicenter collaborative study to construct growth charts and reference values for height, weight and body mass index (BMI) from 3 years of age to adulthood for spontaneous growth of Turkish girls with TS. Methods: Cross-sectional height and weight data of 842 patients with TS, younger than 18 years of age and before starting any therapy, were evaluated. Results: The data were processed to calculate the 3rd, 10th, 25th, 50th, 75th, 90th and 97th percentile values for defined ages and to construct growth curves for height-for-age, weight-for-age and BMI-for-age of girls with TS. The growth pattern of TS girls in this series resembled the growth pattern of TS girls in other reports, but there were differences in height between our series and the others. Conclusion: This study provides disease-specific growth charts for Turkish girls with TS. These disease-specific national growth charts will serve to improve the evaluation of growth and its management with growth-promoting therapeutic agents in TS patients.
Keywords: Turner syndrome; growth charts; body mass index charts; Turkish children; HORMONE TREATMENT; CELIAC-DISEASE; FINAL HEIGHT; STANDARDS; WEIGHT; CHILDREN